Deep Sea Water Improves Abnormalities in Lipid Metabolism through Lipolysis and Fatty Acid Oxidation in High-Fat Diet-Induced Obese Rats - Chang, Wei-Tang; Lu, Tsung-Yueh; Cheng, Ming-Ching; Lu, Hsun-Chi; Wu, Mei-Fang; Hsu, Chin-Lin (Marine drugs, 2017)
Deep sea water (DSW) is a natural marine resource that has been utilized for food, agriculture, cosmetics, and medicine. The aim of this study was to investigate whether DSW has beneficial lipid metabolic effects in an animal model. Our previous in vitro study indicated that DSW significantly decreased the intracellular triglyceride and glycerol-3-phosphate dehydrogenase activity in 3T3-L1 adipocytes. DSW also inhibited the gene levels of adipocyte differentiation, lipogenesis, and adipocytokines, and up-regulated gene levels of lipolysis and fatty acid oxidation. In the present study, the results showed that body weight, liver, adipose tissue, hepatic triglycerides and cholesterol, and serum parameters in the high-fat diet (HFD) + DSW groups were significantly lower compared to the HFD group. Moreover, the fecal output of total lipids, triglycerides, and cholesterol in the HFD + DSW groups was significantly higher than that of the HFD group. Regarding gene expression, DSW significantly increased the gene levels of lipolysis and fatty acid oxidation, and decreased the gene levels of adipocytokine in the adipose tissue of rats with HFD-induced obesity. These results indicate a potential molecular mechanism by which DSW can suppress obesity in rats with HFD-induced obesity through lipolysis and fatty acid oxidation.